A high-scratch-resistant, black-mark-resistant water-based paint composition and a method for preparing the same

CN122878818APending Publication Date: 2026-10-09NIPPON PAINT CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611312828.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

(1)对填料的形貌和粒度分布要求严格,配方兼容性差、原料受限;

Benefits of technology

(1)显著的耐刮擦性能:通过蜡助剂与聚二甲基硅氧烷分散体的协同复配,在低用量下即可获得优异的减摩效果,避免了单一高剂量PDMS带来的表观缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878818A_ABST
    Figure CN122878818A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high scratch-resistant, anti-black mark water-based paint composition and preparation method thereof, belong to water-based building interior wall coating field.The composition includes: the film-forming material with Tg 5 ℃~25 ℃, water, opaque pigment, wax auxiliary agent, polydimethylsiloxane dispersion and anti-black mark filler, and the anti-black mark filler is the composition including zinc sulfide and modified calcium carbonate.The application constructs low friction interface by the synergistic compounding of wax auxiliary agent and polydimethylsiloxane dispersion, utilizes anti-black mark filler to inhibit the transfer and color development of extraneous colorant, and by controlling PVC / CPVC≤0.90, the film-forming material is optimized to the wrapping of filler, and the lightening and black mark caused by metal scratch are inhibited.The composition realizes the comprehensive promotion of scratch resistance, anti-black mark, paint film apparent quality and low VOC / SVOC performance under the premise of not relying on high Tg emulsion and high dose slip agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water-based architectural coatings technology, specifically relating to a water-based coating composition with high scratch resistance and anti-black mark properties and its preparation method. Background Technology

[0002] As consumers increasingly demand aesthetic appeal, durability, and ease of maintenance in their living spaces, water-based architectural coatings are finding wider application in high-touch environments such as homes, children's rooms, schools, hospitals, and commercial spaces. In these environments, the coating film inevitably suffers mechanical damage during its lifespan from furniture friction, object impacts, repeated hand contact, and cleaning, resulting in visible defects such as scratches, abrasions, and black marks, affecting the coating's appearance and the living experience. Therefore, the scratch resistance and black mark resistance of water-based architectural coatings have become core indicators for evaluating product quality and brand competitiveness.

[0003] Specifically, the visible damage suffered by the coating during use can be divided into three categories, each with different physical mechanisms and technical countermeasures: The first category is scratches and abrasions: visible physical damage caused by foreign objects passing over the coating surface, typically manifested as marks formed by cutting, tearing, or squeezing of the paint film surface. Controlling this type of damage mainly depends on the coating's inherent hardness and surface friction coefficient.

[0004] The second type is rubber shavings residue-type black marks: When foreign rubber objects (rubber doorstops, cabinet casters, shoe soles, etc.) rub or bump against the coating surface, the coloring components (carbon black, vulcanizing agent residue, plasticizers, etc.) are transferred to the paint film surface through physical contact and friction, forming an adhesive contamination. Essentially, it is the transfer and residue of foreign substances on the paint film surface. Controlling this type of damage depends on the chemical composition and polarity characteristics of the paint film surface and needs to be suppressed through the regulation of the chemical composition of specific pigments and fillers.

[0005] The third category is metal scratch-induced gloss / blackening: After a metal object (furniture hardware, keys, tableware, coins, etc.) is scratched or rubbed on the paint film surface, no visible damage to the paint film occurs (no obvious scratches, no exposed substrate), but a visible defect of increased gloss or darkened color appears in localized areas. This can be further subdivided into two sub-phenomena: ① Burnishing: Under high local pressure and shear, the paint film surface undergoes plastic compaction and polishing effects, reducing the surface micro-roughness and increasing the specular reflection ratio, thus resulting in increased local gloss. This can be quantitatively characterized by the gloss difference (ΔGloss) before and after burning at 60° / 85°.

[0006] ② Dark spot: It essentially involves two mechanisms: first, the surface of the paint film is compacted, which changes the optical reflection mode; second, pigments and fillers migrate, rearrange their orientation, or are locally exposed during the scratching process, thus forming a dense, low-scattering area in the local area, which appears "black". It can be quantitatively characterized by the difference in gloss (ΔGloss) before and after scratching at 60° / 85°.

[0007] The two types of black marks mentioned above have different generation mechanisms, influencing factors, and technical countermeasures: rubber shavings residue type black marks are mainly affected by the chemical composition and polarity of the paint film surface, and can be suppressed by regulating the chemical composition of specific pigments and fillers; while metal scratch gloss enhancement / black marks are mainly affected by the interfacial encapsulation relationship between the film-forming substances inside the paint film and the pigments and fillers, and need to suppress their migration and surface compaction by fully encapsulating the pigments and fillers by the film-forming substances.

[0008] To improve the scratch resistance of water-based architectural coatings, the field currently focuses on the following three main technical approaches: The first approach involves developing novel high-Tg emulsion resins or wax emulsions to improve the hardness and scratch resistance of the paint film. This approach is costly and time-consuming, and the high-Tg emulsions have poor film-forming properties. It typically requires the addition of large amounts of film-forming aids containing volatile organic compounds (VOCs), leading to an increase in the VOC and semi-volatile organic compound (SVOC) content of the product.

[0009] The second type involves adding a single slip agent (such as polydimethylsiloxane) to the existing latex paint system to reduce the coefficient of friction of the coating surface. However, if a higher slip effect is pursued simply by increasing the amount of this additive, it is easy to cause surface defects such as orange peel and pinholes.

[0010] The third approach involves improving the surface hardness of the paint film by introducing specific inorganic fillers or controlling the particle size distribution of the fillers. This approach has strict requirements on the selection, particle size, surface treatment, and amount of fillers added, and simply increasing the hardness of the fillers cannot effectively suppress visible defects such as black marks.

[0011] A search revealed that the closest prior art to this invention is Chinese invention patent application CN121335956A, which discloses a scratch-resistant and abrasion-resistant coating composition. This method improves the scratch resistance of the coating film by introducing two types of hardening agent particles with different particle sizes and regular morphologies, and compounding them with a water-dispersible polysiloxane. However, this method still has the following shortcomings: (1) Strict requirements are placed on the morphology and particle size distribution of the filler, resulting in poor formulation compatibility and limited raw materials; (2) The two types of "black marks appearing" problems after the scratches occurred were not independently controlled; (3) The synergistic optimization of film-forming substances Tg, VOC and SVOC was not performed; (4) The apparent risks caused by relying solely on high doses of polysiloxane have not been eliminated. Summary of the Invention

[0012] This invention aims to solve the aforementioned problems in the prior art and provides a waterborne coating composition with high scratch resistance and anti-black mark properties, as well as a method for preparing the same. The technical solution of this invention can simultaneously achieve improved scratch resistance, reduced visible defects such as black marks, controllable appearance quality, and synergistic control of VOCs / SVOCs within the same waterborne coating system, without relying on specific morphology high-hardness fillers, without using a single high-dose polysiloxane, and without relying on high-Tg emulsion resins.

[0013] The first objective of this invention is: A water-based coating composition with high scratch resistance and anti-black mark properties is provided, comprising: a. Film-forming material with a glass transition temperature (Tg) of 5℃~25℃; b. Water; c. Opaque pigments; d. Wax additives, the amount of which is 0.5% to 3% of the total weight of the water-based coating composition; e. A polydimethylsiloxane dispersion, used in an amount of 0.5% to 2% of the total weight of the waterborne coating composition; f. Anti-black mark filler, which is a composition comprising zinc sulfide and modified calcium carbonate, wherein the modified calcium carbonate is precipitated calcium carbonate treated with a surface treatment agent; g. Additives, selected from at least one of dispersants, wetting agents, defoamers, pH adjusters, thickeners, rheology modifiers, fungicides, and bactericides and preservatives; The weight ratio of the wax additive to the polydimethylsiloxane dispersion is 1:1 to 3:1, preferably 1:1 to 2:1. Furthermore, the ratio of the pigment volume concentration (PVC) to the critical pigment volume concentration (CPVC) of the water-based coating composition is PVC / CPVC ≤ 0.90, preferably 0.70 to 0.85, to ensure that the emulsion film-forming substance fully encapsulates the anti-black mark filler and the irregular morphology pigment.

[0014] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: It also contains at least one irregularly shaped pigment selected from ultrafine calcite powder, ultrafine barium sulfate, and calcined kaolin, and the total amount of the pigment is not less than 8% of the total weight of the water-based coating composition.

[0015] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: It comprises the following raw material components by weight percentage: Film-forming substance 25%–45%, wax additives 0.5%–3%, polydimethylsiloxane dispersion 0.5%–2%, opaque pigment 15%–25%, zinc sulfide 1%–5%, modified calcium carbonate 3%–10%, ultrafine calcite powder 3%–12%, ultrafine barium sulfate 1%–5%, and additives 0.5%–5%, with the balance being water; the sum of all raw material components is 100%. The opaque pigment is rutile titanium dioxide.

[0016] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The film-forming substance is selected from at least one of styrene-acrylic emulsion, (meth)acrylic emulsion, vinyl acetate emulsion, polyurethane-modified acrylic emulsion, and polyurethane dispersion, and its minimum film-forming temperature (MFFT) is 5°C to 20°C.

[0017] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The minimum film-forming temperature (MFFT) of the film-forming substance is 5°C to 20°C, and it is selected from at least one of styrene-acrylic emulsion, (meth)acrylic emulsion, vinyl acetate emulsion, polyurethane-modified acrylic emulsion, and polyurethane dispersion.

[0018] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The solid content of the polydimethylsiloxane dispersion is 45-85% by weight.

[0019] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The zinc sulfide has a D50 of 0.8–1.5 μm and a Mohs hardness of ≥3.

[0020] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The surface treatment agent is selected from at least one of stearic acid, aluminate and silane coupling agent.

[0021] The further optimization of the water-based coating composition with high scratch resistance and anti-black mark properties described in this invention is as follows: The emulsion particle size of the film-forming substance is Dv50≤300nm, the average particle size D50 of the anti-black mark filler is 0.8μm~3.0μm, and the ratio of the emulsion particle size Dv50 to the average particle size D50 of the anti-black mark filler is Dv50 / D50≤0.2, preferably Dv50 / D50≤0.1, so as to match the micron-sized particle size of the anti-black mark filler and the extender pigment to form an effective encapsulation structure.

[0022] The second objective of this invention is: A method for preparing the aforementioned highly scratch-resistant and anti-black-mark waterborne coating composition is provided, comprising the following preparation steps: S1. Pre-dispersion stage: Water and a portion of the additives are mixed under low shear conditions of 500-800 r / min to obtain a pre-dispersion. S2. Grinding and Dispersion Stage: Under high shear conditions of 1300-1600 r / min, opaque pigments and anti-black mark fillers are added to the pre-dispersion liquid and ground to the required particle size (e.g., fineness ≤50μm) to obtain a grinding slurry; S3. Preparation stage: Under low shear conditions of 500-800 r / min, add the remaining additives, film-forming substances, wax additives, and polydimethylsiloxane dispersion to the grinding slurry and mix evenly; S4. Thickening stage: Add water or thickener to adjust the viscosity to the target range of 95-105 KU to obtain the water-based coating composition with high scratch resistance and anti-black mark properties.

[0023] This invention achieves simultaneous improvement in scratch resistance, reduction of visible defects such as black marks, controllable coating film appearance quality, and synergistic control of VOC / SVOC within the same water-based coating system through the organic combination of the following four mechanisms: (a) Synergistic friction-reducing system of wax additives and polydimethylsiloxane dispersion The wax additives are oriented in the form of microparticles on the surface of the paint film, providing a low-friction surface layer on a macroscopic scale; the polydimethylsiloxane dispersion fills the gaps between the wax additives at the molecular scale, reducing interfacial tension. Together, they form a controlled low-friction interface, achieving scratch resistance superior to either a single wax additive or a single polysiloxane, even at a much lower dosage. In this invention, the dosage of polydimethylsiloxane is kept at a low level of 0.5–2%, avoiding surface defects such as orange peel and pinholes caused by high doses of polydimethylsiloxane alone.

[0024] (II) Anti-black mark filler combination Zinc sulfide and modified calcium carbonate were introduced into the pigment and filler system as a dual-anti-black-stain filler combination. Zinc sulfide, as a white multifunctional pigment, effectively reduces the adsorption and color development of coloring components such as carbon black and residual vulcanizing agents from rubber materials on the coating surface due to its surface chemical properties (refractive index approximately 2.37, low polarity). Modified calcium carbonate, after surface treatment with stearic acid or aluminate, exhibits an oleophobic surface, further reducing the transfer and adhesion of foreign coloring components. The two work synergistically to reduce the transfer and color development of foreign rubber material coloring components on the coating surface at the chemical composition level. Even with slight scratches on the coating surface, the appearance of black marks caused by residual rubber shavings can still be significantly controlled.

[0025] (III) Encapsulation and load-bearing regulation of the film-forming substance-inorganic particle interface This invention optimizes the wetting and film-forming matching relationship between the film-forming substance and inorganic particles, ensuring that the inorganic particles are fully encapsulated by the emulsion film-forming substance during film formation. Specific control parameters include: the ratio of the system pigment volume concentration (PVC) to the critical pigment volume concentration (CPVC), PVC / CPVC ≤ 0.90, to ensure sufficient encapsulation of the emulsion film-forming substance against black mark fillers and irregularly shaped extender pigments. When a metal object scratches across the coating surface, or when high local pressure and shear are applied: ① Fully encapsulated pigments and fillers are less likely to migrate, rearrange their orientation, or be locally exposed under shear stress, thus avoiding the low-scattering, high-absorption dense area (i.e. the core cause of black scratches) caused by the local accumulation of pigments and fillers in the scratching area. ② Film-forming substances participate in local load-bearing and energy dispersion, reducing the probability of plastic compaction and mirror polishing of the paint film surface due to high pressure (i.e., the core cause of scratch-and-grind enhancement); ③ Even if slight surface compaction occurs, the optical reflection properties of the paint film will not deviate significantly from the original state because the distribution and orientation of the filler do not change significantly.

[0026] These three effects work together to suppress the formation of metal polishing and black marks from scratching, which can be quantitatively characterized by the change in gloss (ΔGloss) and color difference (ΔE) before and after scratching at 60° / 85°.

[0027] (iv) Low Tg film-forming substance adaptation and synergistic reduction of SVOC The scratch resistance of this invention is mainly provided by the mechanisms described in (I) to (III) above, and does not depend on the bulk hardness of the high Tg emulsion resin. Therefore, film-forming materials with lower Tg (range 5–25°C) can be used, correspondingly reducing the amount of VOC / SVOC film-forming aids, thereby achieving a synergistic reduction in VOC, especially SVOC, content. In all embodiments of this invention, the VOC content is less than 2 g / L, and the SVOC content is less than 2 g / L, achieving an industry-leading environmental protection level.

[0028] Compared with the prior art, the present invention has the following technical features and effects: (1) Significant scratch resistance: Through the synergistic compounding of wax additives and polydimethylsiloxane dispersion, excellent friction reduction effect can be obtained at low dosage, avoiding the appearance defects caused by high dosage of PDMS alone.

[0029] (2) Excellent anti-black mark performance: By introducing anti-black mark fillers such as zinc sulfide and modified calcium carbonate, the black marks of rubber shavings residue are suppressed from the chemical level; by optimizing the film-forming substance to encapsulate the filler (PVC / CPVC ≤ 0.90), the metal scratching gloss enhancement / black marks are suppressed.

[0030] (3) Low VOC / SVOC environmental performance: Low Tg film-forming material is used, and film can be formed without adding VOC / SVOC film-forming aids, thus achieving synergistic reduction of VOC and SVOC.

[0031] (4) Good formulation compatibility: It does not rely on fillers with special morphology and particle size distribution, and is highly compatible with existing architectural coating formulation systems, which facilitates industrial production and formulation upgrades.

[0032] Terminology definition: The term "black mark" in this invention is a broad concept, encompassing visual defects generated under the following two different physical mechanisms: (1) Rubber shavings residue type black marks: refers to the adhesion type of contamination formed when the coloring components of foreign rubber objects are transferred to the paint film surface through physical contact and friction when they are rubbed or bumped on the coating film surface.

[0033] (2) Metal scratches / black marks: refers to the visible defects that appear in local areas, such as increased gloss or darkened color, after a metal object is scratched or rubbed on the paint film surface without any visible damage to the paint film. Attached Figure Description

[0034] Figure 1 This is a comparison diagram showing the effect of the water-based coating composition emulsion of the present invention (right figure) on filler inclusion between it and the emulsion in conventional products (left figure). Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and comparative experiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention. Unless otherwise specified, the reagents, equipment, and methods used in this invention are conventional reagents, equipment, and general methods in this technical field. Unless otherwise specified, all components in this invention are expressed as weight percentages (wt%), and the sum of all raw material components in the formulations of each embodiment is 100%.

[0036] Unless otherwise specified, the dispersants, wetting agents, defoamers, thickeners, rheology modifiers, pH adjusters, mildew inhibitors, and bactericides and preservatives described in this invention are all conventional additives in the field of water-based architectural coatings. Their dosage can be selected according to the conventional dosage in the field, typically 0.05% to 1.5% of the total weight of the composition, and the dosage shown in the examples is the preferred embodiment.

[0037] In this invention, the pigment volume concentration (PVC) is obtained using conventional volume calculation methods in the coatings industry, i.e., the volume of all non-volatile pigments and fillers in the formulation divided by the sum of the pigment / filler volume and the dry film volume of the film-forming substance. The critical pigment volume concentration (CPVC) is determined using the oil absorption value method or empirical formula commonly used in the field, reflecting the upper limit of pigment volume concentration when the emulsion film-forming substance just fills the gaps between pigments and fillers. In the examples, the PVC / CPVC ratio is calculated from the density, oil absorption value, and dosage of the formulation components.

[0038] In this invention, the average particle size D50 of the anti-black-stain filler refers to the volume-weighted average particle size calculated based on the weight ratio of zinc sulfide and modified calcium carbonate in the formulation, or, when the anti-black-stain filler is a single component, its own D50. The emulsion particle size Dv50 of the film-forming substance is determined by dynamic light scattering.

[0039] To further clarify the availability and preferred dosage range of each raw material component, this invention provides the following table of raw material source examples (Table 1), wherein the manufacturers and product names listed are merely examples of raw material sources to demonstrate the availability of the raw materials described in this invention and do not constitute a limitation on the scope of protection of this invention: Table 1 Examples of Raw Material Sources

[0040] Note: This formulation does not include VOC / SVOC film-forming aids, which are the core of this invention to achieve SVOC-free.

[0041] Examples 1-4

[0042] The waterborne coating composition of the present invention was prepared according to the formulation shown in Table 2 and the preparation process described below.

[0043] Preparation process:

[0044] Add an appropriate amount of pure water to the container, and add the dispersant, wetting agent, defoamer A, pH adjuster and hydroxyethyl cellulose HEC in sequence while stirring at 500 r / min. Stir for 3 to 5 minutes to fully dissolve and disperse the dispersant. Increase the rotation speed to 800 r / min and add the powders in the following order: rutile titanium dioxide, zinc sulfide, modified calcium carbonate, ultrafine calcite powder, and ultrafine barium sulfate. After all the powders have been added, increase the rotation speed to 1300–1600 r / min and disperse at high speed for 20–30 minutes, then grind until the fineness is ≤50 μm (as determined according to GB / T 1724—2019). After high-speed dispersion, film-forming material, wax additive, and PDMS dispersion are added sequentially at a stirring speed of 700 r / min, stirring for 2-3 minutes after each addition. Then, defoamer B, bactericide and preservative, and fungicide are added sequentially, and stirred for 5 minutes. Finally, add the remaining pure water and slowly add the rheology modifier to adjust the viscosity to 100±5 KU (as determined according to GB / T9269—2009), and stir the mixture for 10 to 15 minutes until homogeneous. After filtration and packaging, the highly scratch-resistant water-based interior wall paint of this invention is obtained.

[0045] Table 2. Formulation of the Example (by weight, total weight: 100 parts)

[0046] Comparative Examples 1-6 The preparation methods of Comparative Examples 1-6 are basically the same as those of Example 1, with the main difference being that the formulations of Comparative Examples 1-6 are shown in Table 3. The types and amounts of "other additives" mentioned in Comparative Examples 1-6 are the same as those in Example 1 (see the Example 1 column in Table 2, including dispersants, wetting agents, defoamer A, defoamer B, pH adjusters, HEC thickeners, HEUR rheology modifiers, fungicides, and bactericides / preservatives).

[0047] Table 3 Comparative formulations (by weight, total weight: 100 parts)

[0048] Table 4 Performance Testing Methods

[0049] Test results: The performance test results of each embodiment and comparative example are shown in Tables 5 and 6.

[0050] Table 5 Performance data of the embodiments

[0051] Table 6 Comparative Performance Data

[0052] *Note: The lowest film-forming temperature (MFFT) of resin C used in Comparative Example 6 is 38°C. After adding 3 parts by weight of SVOC-containing film-forming aid, the effective MFFT of the system is reduced to about 23°C to meet the requirements for film formation at room temperature.

[0053] Results analysis: 1. Synergistic effect of wax + PDMS The comparison between Example 1 and Comparative Example 1 (double blank, neither wax nor PDMS), Comparative Example 2 (wax only), and Comparative Example 3 (PDMS only) shows that the scratch resistance improvement produced by the combination of wax and PDMS is significantly greater than the simple additive effect of using either alone, proving that there is a synergistic effect. In the supplementary double blank control (Comparative Example 1), the metal scratch resistance was only "good" and the rubber scratch resistance was "poor," while both of Example 1 were "excellent," further proving that the scratch resistance improvement produced by the combination of wax and polydimethylsiloxane is not a simple additive effect of the two, but rather a synergistic effect. At the same time, the comparison between the orange peel defects of Comparative Examples 3 and 4 and the defect-free appearance of the paint film of Examples 1-4 proves that the wax + PDMS combination can achieve excellent friction reduction effect at a low PDMS dosage, avoiding the apparent risks of using high-dose PDMS alone.

[0054] Specific test results show that: Example 1 achieved "excellent" level in both metal scratch resistance and rubber scratch resistance, while Comparative Example 1 (no wax and no PDMS) was only "good" and "poor", Comparative Example 2 (wax only) was "excellent" and "qualified", and Comparative Example 3 (PDMS only) was "excellent" and "excellent", but orange peel defect appeared.

[0055] 2. Independent contribution of anti-black-stain filler A comparison of Example 1 and Comparative Example 5 (using ordinary heavy calcium carbonate in equal amounts to replace zinc sulfide and modified calcium carbonate) shows that modified calcium carbonate, as an anti-black-mark filler, has an independent inhibitory contribution to the appearance of black marks on rubber objects. Comparative Example 5 received a "good" rating for rubber black marks (lower than "excellent" in Example 1), with metal abrasion 60° ΔGloss ≥ 8.0 GU and 85° ΔGloss ≥ 10.0 GU, while Example 1 showed ≤1.5 GU and ≤2.5 GU, respectively. This comparison independently demonstrates the independent technical contribution of anti-black-mark fillers in inhibiting both rubber shavings-related black marks and metal abrasion-induced gloss / black marks, a contribution that cannot be achieved simply by increasing the amount of wax or PDMS.

[0056] Specific test results show that: Example 1 has "excellent" rubber scratch resistance, with metal abrasion resistance of 60°ΔGloss ≤ 1.5 GU and 85°ΔGloss ≤ 2.5 GU; while Comparative Example 5 (without anti-black mark filler) has reduced rubber scratch resistance to "good", with metal abrasion resistance of 60°ΔGloss ≥ 8.0 GU and 85°ΔGloss ≥ 10.0 GU, and obvious black marks appear.

[0057] 3. Metal scratch enhancement / interface encapsulation suppression of black marks A comparison of the metal scratch ΔGloss of Example 1 and Comparative Example 5 shows that the 60° ΔGloss of Example 1 is only about 1 / 4 of that of Comparative Example 5 (≤1.5 GU vs ≥8.0 GU), and the 85° ΔGloss is only about 1 / 4 of that of Comparative Example 5 (≤2.5 GU vs ≥10.0 GU). This demonstrates that the low Tg emulsion film-forming material of the present invention effectively encapsulates the zinc sulfide + modified calcium carbonate dual anti-black-scratch filler (PVC / CPVC ≤0.90), which can effectively inhibit the migration, orientation rearrangement, and local exposure of pigments and fillers during metal scratching, and avoid local gloss increase caused by plastic compaction of the paint film surface. In contrast, in Comparative Example 5, because zinc sulfide + modified calcium carbonate is replaced by ordinary calcium carbonate in equal amounts, the refractive index matching, surface chemical properties, and the encapsulation relationship of the film-forming material with the filler change significantly. Pigments and fillers are more likely to migrate and be exposed under shearing action, resulting in obvious metal scratch gloss enhancement and black marks. This comparison independently demonstrates the independent technical contribution of the film-forming substance-inorganic particle interface encapsulation and load regulation in suppressing metal scratches and brightening / blackening marks, and this contribution cannot be achieved by simply increasing the amount of wax or PDMS.

[0058] Specific test results show that the metal scratching 60°ΔGloss (≤1.5 GU) and 85°ΔGloss (≤2.5 GU) of Example 1 are much lower than those of Comparative Example 5 (≥8.0 GU and ≥10.0 GU), with a reduction of more than 75%.

[0059] 4. Advantages of low Tg + SVOC-free The comparison between Examples 1 and 2 and Comparative Example 6 (high Tg resin Tg≈40℃ + 3 parts of SVOC film-forming aid) shows that the present invention can form a film without adding any VOC film-forming aid by using a low Tg emulsion (Tg=5~15℃, MFFT=5~15℃) and without reducing the scratch resistance.

[0060] Specific test results show that: the VOC content of Example 1 is <2g / L and the SVOC content is <2g / L, while the VOC content of Comparative Example 6 is 4.5g / L and the SVOC content is as high as 82g / L. This invention achieves the simultaneous achievement of "high scratch resistance + SVOC-free".

[0061] 5. Robustness of resin type The comparison between Examples 1 and 3 (Resin A system, Tg≈5℃) and Examples 2 and 4 (Resin B system, Tg≈15℃) shows that the technical solution of the present invention can achieve a scratch resistance rating of "excellent" or "good" under different Tg ranges (5℃ and 15℃) and different wax / PDMS ratios (2:1 and 1:1), proving that the present invention has good formulation robustness.

[0062] 6. Verification of PVC / CPVC limits The PVC / CPVC ratios in Examples 1-4 of this invention range from 0.733 to 0.771, all meeting the requirement of PVC / CPVC ≤ 0.90 as defined in this technical solution. The metal scratching 60° ΔGloss of each example is ≤ 1.5 GU, and the 85° ΔGloss is ≤ 2.5 GU, demonstrating that within this PVC / CPVC range, the film-forming material adequately encapsulates the pigments and fillers, effectively suppressing the formation of gloss enhancement / black marks from metal scratching.

[0063] 7. Boundary verification of PVC / CPVC limits To further verify the critical significance of the limit PVC / CPVC ≤ 0.90 in claim 1, this invention specifically set up a set of comparative experiments: Based on the same formulation and process as Example 1, only the amount of film-forming substance (resin A) was reduced from 38 parts to 25 parts, while the amounts of other components remained unchanged. Water was added to make the total weight 100 parts, and the preparation process was the same as in Example 1. According to the PVC / CPVC calculation method described in this invention, the PVC of this comparative formulation was calculated to be 48.70%, and the PVC / CPVC ratio was 0.949, exceeding the upper limit of 0.90 set by this technical solution. Since the only variable between this comparative formulation and Example 1 is the amount of film-forming substance (38 parts → 25 parts), while the other components (wax additives, PDMS dispersion, anti-black-stain filler, additives, etc.) and preparation process are exactly the same, the performance difference between the two can only be attributed to the change in PVC / CPVC.

[0064] Test results show that after the PVC / CPVC ratio exceeded 0.90, the 60° ΔGloss of the comparative formulation increased from ≤1.5 GU in Example 1 to ≥5.0 GU, and the 85° ΔGloss increased from ≤2.5 GU to ≥7.0 GU. Both metal scratch resistance and rubber scratch resistance decreased from "excellent" to "qualified". Since all variables except the amount of film-forming material were controlled, the above performance deterioration can only be attributed to the fact that after the PVC / CPVC ratio exceeded 0.90, the film-forming material no longer adequately encapsulated the pigments and fillers, leading to migration, orientation rearrangement, and local exposure of the pigments and fillers under metal scratching, thus causing gloss enhancement and black marks.

[0065] This comparative experiment independently proved that PVC / CPVC≤0.90 is a necessary condition to ensure that the film-forming substance fully encapsulates the pigments and fillers and to inhibit metal scratches and enhance gloss / black marks.

[0066] Furthermore, by comparing Examples 1-4 (PVC / CPVC=0.733-0.771) with Comparative Example 5 (PVC / CPVC=0.679, where ΔGloss≥8.0 due to filler replacement), it can be seen that PVC / CPVC≤0.90 is a necessary condition, but not a sufficient condition. Under the premise of meeting this limit, it is also necessary to use specific anti-black-stain fillers (zinc sulfide + modified calcium carbonate) and synergistic compounding of wax additives and PDMS to simultaneously achieve excellent scratch resistance, anti-black-stain performance and low VOC / SVOC environmental performance.

[0067] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A water-based coating composition with high scratch resistance and anti-black mark properties, characterized in that: include: a. Film-forming material with a glass transition temperature (Tg) of 5℃~25℃; b. Water; c. Opaque pigments; d. Wax additives, the amount of which is 0.5% to 3% of the total weight of the water-based coating composition; e. A polydimethylsiloxane dispersion, used in an amount of 0.5% to 2% of the total weight of the waterborne coating composition; f. Anti-black mark filler, which is a composition comprising zinc sulfide and modified calcium carbonate, wherein the modified calcium carbonate is precipitated calcium carbonate treated with a surface treatment agent; g. Additives, selected from at least one of dispersants, wetting agents, defoamers, pH adjusters, thickeners, rheology modifiers, fungicides, and bactericides and preservatives; The weight ratio of the wax additive to the polydimethylsiloxane dispersion is 1:1 to 3:

1. Furthermore, the ratio of the pigment volume concentration (PVC) to the critical pigment volume concentration (CPVC) of the water-based coating composition is PVC / CPVC ≤ 0.

90.

2. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: It also contains at least one irregularly shaped pigment selected from ultrafine calcite powder, ultrafine barium sulfate, and calcined kaolin, and the total amount of the pigment is not less than 8% of the total weight of the water-based coating composition.

3. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: It comprises the following raw material components by weight percentage: Film-forming substance 25%–45%, wax additives 0.5%–3%, polydimethylsiloxane dispersion 0.5%–2%, opaque pigment 15%–25%, zinc sulfide 1%–5%, modified calcium carbonate 3%–10%, ultrafine calcite powder 3%–12%, ultrafine barium sulfate 1%–5%, and additives 0.5%–5%, with the balance being water; the sum of all raw material components is 100%. The opaque pigment is rutile titanium dioxide.

4. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The minimum film-forming temperature (MFFT) of the film-forming substance is 5°C to 20°C, and it is selected from at least one of styrene-acrylic emulsion, (meth)acrylic emulsion, vinyl acetate emulsion, polyurethane-modified acrylic emulsion, and polyurethane dispersion.

5. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The wax additive is selected from at least one of polyethylene wax emulsion, PTFE modified wax emulsion, palm wax emulsion, amide wax emulsion, and polyamide wax emulsion.

6. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The solid content of the polydimethylsiloxane dispersion is 45-85% by weight.

7. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The zinc sulfide has a D50 of 0.8–1.5 μm and a Mohs hardness of ≥3.

8. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The surface treatment agent is selected from at least one of stearic acid, aluminate and silane coupling agent.

9. The water-based coating composition with high scratch resistance and anti-black mark properties according to claim 1, characterized in that: The emulsion particle size of the film-forming substance is Dv50≤300nm, the average particle size D50 of the anti-black mark filler is 0.8μm~3.0μm, and the ratio of the emulsion particle size Dv50 to the average particle size D50 of the anti-black mark filler is Dv50 / D50≤0.

2.

10. A method for preparing a water-based coating composition with high scratch resistance and anti-black mark properties as described in any one of claims 1 to 9, characterized in that: The preparation steps include the following: S1. Pre-dispersion stage: Water and a portion of the additives are mixed under low shear conditions of 500-800 r / min to obtain a pre-dispersion. S2. Grinding and dispersing stage: Under high shear conditions of 1300-1600 r / min, opaque pigments and anti-black mark fillers are added to the pre-dispersion liquid and ground to the required particle size to obtain a grinding slurry; S3. Preparation stage: Under low shear conditions of 500-800 r / min, add the remaining additives, film-forming substances, wax additives, and polydimethylsiloxane dispersion to the grinding slurry and mix evenly; S4. Thickening stage: Add water or thickener to adjust the viscosity to the target range of 95-105 KU to obtain the water-based coating composition with high scratch resistance and anti-black mark properties.

Citation Information

Patent Citations

  • Scratch-resistant and scratch-resistant coating composition

    CN121335956A